Pandemi Covid, penunjang atau penghambat bagi para peneliti dunia medis - Adi Nugroho, Prasetyo (LIBRARIA : Jurnal Ilmu Perpustakaan dan Informasi, 2021)
The corona virus restrain the movement of people. Higher education has also been affected, especially academics. The repository as a data provider is expected to be a solution to data provider problems during the pandemic. This study aims to analyze whether the repository of scientific papers has an effect on improving the scientific work of medical academics or not. This study uses a quantitative method with a bibliometric approach. The sample of this study is the repository of scientific papers at Gadjah Mada University. The sample is divided into two, scientific papers contain the keyword "medical", and the keyword "nutrition". Samples were analyzed based on 2 criteria, the number of publications and study programs at most contributed papers with the keywords above. The study results show that the repository of scientific papers does not cause an increase in the number of repositories, but causes a decrease. One of the things is due to social restrictions that reduce the space for academics to move, especially in access to facilities that are usually provided by the campus. Both in terms of "medical" and "nutrition" has decreased. In addition, this study also found that non-medical fields of study also have the largest repository in library databases.